Synthesis of TiO2 Thin Films Nanoparticles with Different Layers using Simple Sol-Gel Method - Abdulsada, Rajaa Obayes; Hassan, Thamir A.A. (Iraqi Journal of Science, 2021)
In this study, titanium dioxide (TiO2 (are synthesized by sol– gel simple method. Thin films of sol, gel, and sol- gel on relatively flat glass substrates are applied with Spin coating technique with multilayers. The optical and morphological properties (studied using AFM) of TiO2 layers show good properties, with particles diameters less than 4 nm for all prepared samples and have maximum length 62 nm for TiO2 gel thin films of three layers. The results show low roughness values for all films especially for 4 layers sol (8.37nm), which improve the application in dye sensitive solar cell (DSSc) .